(untitled) (Indian Journal of Public Health Research & Development, 2020)
This study amied to measure the concentration of heavy metals (Pb, Cd) and certain biochemical variables in blood and nails of(50) samples(male and female) of workers (who were in risk of exposition to these heavy metals) from Northern Gas Company in Kirkuk city/Iraq. Flame atomic absorption spectrometer was used for measuring these elements. The results showed significant differences (P < 0.01) in the concentration of lead and cadmium in the studied samples (whole blood and nails) of workers compared to the control group. The concentration of lead and cadmium were higher in blood and Nails. As of the biochemical variables, significant differences (P < 0.05) showed in the concentration of antioxidant enzyme (SOD) in serum. As of oxidative stress (MDA), results showed significant differences (P < 0.05) in serum, the highest value of (MDA) was recorded in serum samples.